2013
DOI: 10.1097/igc.0b013e318277608b
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on the Possible Association Between In Vitro Fertilization and Cancer Risk

Abstract: This meta-analysis suggests that there is no significant association between IVF and cancer risk. A possible beneficial effect was shown in the subgroup of breast cancer meta-analysis. Excess risk of ovarian cancer was observed in the analysis of all the studies and subgroups. Special attention should be made to women who may be diagnosed with cancer during or shortly after IVF treatment. Studies of high methodological quality with larger population and longer follow-up are required to provide more evidences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Some studies suggested an association among the use of ovulation-inducing drugs, IVF, and ovarian cancer risk, but only few cases of ovarian cancer have been described in women followed in IVF programs [41,42]. Therefore the relationship between IVF and development of ovarian cancer is still under investigation (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies suggested an association among the use of ovulation-inducing drugs, IVF, and ovarian cancer risk, but only few cases of ovarian cancer have been described in women followed in IVF programs [41,42]. Therefore the relationship between IVF and development of ovarian cancer is still under investigation (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two recent meta-analyses have recently been published on this topic [41,42]. In the study of Siristatidis et al [41], nine cohort studies were analyzed (109969 women exposed to IVF with 76 cases of ovarian cancer).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis involving eight cohort studies including almost 750,000 participants failed to find a significant association between cancer risk and women undergoing IVF [27]. Utilizing data from Western Australia, other investigators found no evidence of an increased risk of ovarian cancer following IVF in women who give birth but some uncertainty (nonsignificant) regarding ovarian cancer following IVF in women remaining nulliparous [28].…”
Section: Risks Of Birth Defects After Artmentioning
confidence: 95%